Forensic Application of Epidermal Ubiquitin Expression to Determination of Wound Vitality in Human Compressed Neck Skin - Zhang, Siying; Ishida, Yuko; Ishigami, Akiko; Nosaka, Mizuho; Kuninaka, Yumi; Hata, Satoshi; Yamamoto, Hiroki; Hashizume, Yumiko; Matsuki, Jumpei; Yasuda, Haruki; Kimura, Akihiko; Furukawa, Fukumi; et al. (Frontiers in Medicine, 2022)
Ubiquitin is a member of the heat shock protein family and is rapidly induced by various types of stimuli, including ischemic and mechanical stress. However, its significance in determining wound vitality of neck compression skin in forensic pathology remains unclear. We immunohistochemically examined the expression of ubiquitin in the neck skin samples to understand its forensic applicability in determining wound vitality. Skin samples were obtained from 53 cases of neck compression (hanging, 42 cases; strangulation, 11 cases) during forensic autopsies. Intact skin from the same individual was used as the control. Ubiquitin expression was detected in 73.9% of keratinocytes in intact skin samples, but only in 21.2% of keratinocytes in the compression regions, with statistical differences between the control and compression groups. This depletion in the case of neck compression may be caused by the impaired conversion of conjugated to free ubiquitin and failure of de novo ubiquitin synthesis. From a forensic pathological perspective, immunohistochemical examination of ubiquitin expression in the skin of the neck can be regarded as a valuable marker for diagnosing traces of antemortem compression.